The impact of people’s bank of China’s policies on Chinese stock market volatility - Wang, Zian (2024)
The COVID-19 pandemic serves as the main backdrop for this article's investigation of how the People's Bank of China's policies affect stock market volatility. This study used the CSI300 and S&P500 stock index data from 2018 to 2023 and the ARCH, GARCH, TGARCH, and EGARCH models to analyze the index's overall volatility from a macro perspective. From a micro perspective, it used Event Study Analysis to examine the effects of particular policies on the CSI300 index's volatility. Because CSI300 is a typical index for the Chinese stock market and S&P500 is an index that has been tracked in the United States since 1957, CSI300 was chosen as the benchmark. The S&P 500 has more businesses and more diversified industries than the Dow Jones Index, which helps to spread risk and enable it to reflect movements in the broader market. According to macroscopic experimental findings, volatility is frequently more affected by unpleasant news. The results of a microscopic experiment indicate that each policy announcement will have a large impact on index volatility, but the effects of receiving good news and negative news are same. This is also a result of how the epidemic and the Chinese financial market are affected by the state of the world economy. Efficiency suffers as a result.